Digital notetaking in lectures: how students adapt to a multi-faceted university learning environment - Beckie Arden; Jennifer Norris; Steve Cole; Simon C. Gamble (Cogent Education, 2024)
University students are increasingly taking a digital approach to notetaking in lectures, influenced by technological developments, environmental sustainability, and the Covid-19 pandemic. This research aims to understand the ways in which students currently make digital notes and identify barriers to digital notetaking from a student perspective. Data were collected between January and May 2022 through a questionnaire (n = 123) and four focus groups (n = 17), including both undergraduate and postgraduate students representing a wide range of degree subjects. We find that students’ decisions about when and how to take digital notes are multi-faceted and change over time, responding to three interrelated aspects of the university learning environment: (1) perceived social pressure, (2) lecture content, delivery, and future assessment, and (3) affordances of digital technologies. We argue that this has implications for supporting students’ notetaking skills development, especially at the transition to university, as well as for lecturers’ pedagogical decisions around uses of technology in both live and recorded lectures. A nuanced approach to the ‘digital divide’ must consider equality of access to digital technologies that meet students’ multiple academic needs, as well as supporting students’ agency in finding their own solutions.